CURRICULAR INNOVATION AND ENVIRONMENTAL EDUCATION IN AGROECOLOGY COURSES - Spazziani, Maria de Lourdes [UNESP]; Chova, L. G.; Martinez, A. L.; Torres, I. C. (Iated-int Assoc Technology Education & Development, 2013)
The professional farmer and agricultural sciences are fundamental poles of the process of rural development. The curricula of courses in the field of agricultural sciences need to foster interaction between academic knowledge and knowledge accumulated through experience family farmer, through the inclusion of studies or disciplines of agroecology and environmental education. These two fields can help to construct a model of sustainable socio appropriate to the reality of family farming. This article examines curricular features of four undergraduate courses in Agricultural Sciences through research, interviews and exchanges of professors from different regions of the country, which show the priority in active teaching methods and practices in research and extension family farming; diversity in social origin of the students; presence of strong disciplines of human and social areas. We noticed the importance of environmental education; however, there is an absence of this topic in the official curriculum.
Keywords: university; curriculum; training